Could Early Antiretroviral Therapy Entail More Risks than Benefits in Sub-Saharan African HIV-Infected Adults? A Model-Based Analysis. Issue 1 (January 2013) - Anglaret, Xavier; Scott, Callie A; Walensky, Rochelle P; Ouattara, Eric; Losina, Elena; Moh, Raoul; Becker, Jessica E; Uhler, Lauren; Danel, Christine; Messou, Eugene; Eholié, Serge; Freedberg, Kenneth A
Background: Initiation of antiretroviral therapy (ART) in all HIV-infected adults, regardless of CD4 + T-cell count, is a proposed strategy for reducing HIV transmission. We investigated the conditions under which starting ART early could entail more risks than benefits for patients with high CD4 + T-cell counts. Methods: We used a simulation model to compare ART initiation upon entry to care ('immediate ART') to initiation at CD4 + T-cell count ≤350 cells/μl ('WHO 2010 ART') in African adults with CD4 + T-cell counts >500 cells/μl. We varied inputs to determine the combination of parameters (population characteristics, conditions of care, treatment outcomes) that would result in higher 15-year mortality with immediate ART. Results: The 15-year mortality was 56.7% for WHO 2010 ART and 51.8% for immediate ART. In one-way sensitivity analysis, lower 15-year mortality was consistently achieved with immediate ART unless the rate of fatal ART toxicity was >1.0/100 person-years, the rate of withdrawal from care was >1.2-fold higher or the rate of ART failure due to poor adherence was >4.3-fold higher on immediate than on WHO 2010 ART. In multi-way sensitivity analysis, immediate ART led to higher mortality when moderate rates of fatal ART toxicity (0.25/100 person-years) were combined with rates of withdrawal from care >1.1-fold higher and rates of treatment failure >2.1-fold higher on immediate than on WHO 2010 ART. Conclusions: In sub-Saharan Africa, ART initiation at entry into care would improve long-term survival of patients with high CD4 + T-cell counts, unless it is associated with increased withdrawal from care and decreased adherence. In early ART trials, a focus on retention and adherence will be crucial.